Tirofiban and Rivaroxaban use in the management of right coronary artery thrombus as a primary manifestation of essential thrombocythemia - Muhummad Nasir Rahman; Javed, Maleeha (Journal of the Pakistan Medical Association, 2022)
A 45 year old male with hypertension was presented to our centre with a recent inferior wall myocardial infarction (IWMI) and post infarction angina. Invasive coronary angiography revealed an occluded proximal right coronary artery (RCA) with high thrombus burden, in the absence of obstructive disease in the remaining coronary vasculature. Based on raised platelet counts of 923,000/microliter and positive Janus kinase (JAK 2- V617) mutations tested by polymerase chain reaction (PCR), a diagnosis of essential thrombocythemia (ET) was made. A therapeutic strategy of aspiration thrombectomy along with I/V Tirofiban was used for three days, followed by reassessed angiogram and percutaneous coronary intervention (PCI) with drug eluting stent (DES) placement was applied. In addition to dual antiplatelet and statin therapy, patient was treated with Rivaroxaban 15 mg once daily for a month and Hydroxyurea 500mg twice daily. At one month follow up, patient was asymptomatic, Continue...